Climate impacts of changing aerosol emissions since 1996. Issue 13 (14th July 2014) - Kühn, T.; Partanen, A.‐I.; Laakso, A.; Lu, Z.; Bergman, T.; Mikkonen, S.; Kokkola, H.; Korhonen, H.; Räisänen, P.; Streets, D. G.; Romakkaniemi, S.; Laaksonen, A.
Abstract Increases in Asian aerosol emissions have been suggested as one possible reason for the hiatus in global temperature increase during the past 15 years. We study the effect of sulphur and black carbon (BC) emission changes between 1996 and 2010 on the global energy balance. We find that the increased Asian emissions have had very little regional or global effects, while the emission reductions in Europe and the U.S. have caused a positive radiative forcing. In our simulations, the global‐mean aerosol direct radiative effect changes by 0.06 W/m2 during 1996 to 2010, while the effective radiative forcing (ERF) is 0.42 W/m2. The rather large ERF arises mainly from changes in cloudiness, especially in Europe. In Asia, the BC warming due to sunlight absorption has largely offset the cooling caused by sulphate aerosols. Asian BC concentrations have increased by a nearly constant fraction at all altitudes, and thus, they warm the atmosphere also in cloudy conditions.